Frequency of visits by ants and their effectiveness as pollinators of Condalia microphylla Cav. - Chacoff, Natacha Paola (2014)
The effect of a pollinator species on a plant depends on their interaction frequency and the pollinator's effectiveness. The role of ants as pollinators is highly variable, in some cases they act as true pollinators and in others as antagonists damaging flowers, robbing nectar or disrupting pollination. Pollinator visitation frequency has been demonstrated as the most important factor determining their impact on plants. Ants are commonly seen as visitors of the desert shrub Condalia microphylla, but their effectiveness as pollinators is unknown. In this study we assess the quantitative and qualitative role of ants and other winged flower visitors as pollinators of C. microphylla by experimentally quantifying their contribution to fruit production. The study was conducted in the Monte Desert of Villavicencio Nature Reserve, Mendoza, Argentina. A diverse assemblage of insects visited flowers of C. microphylla, including bees, ants, flies, beetles and vespids. Ants (Camponotus mus and Camponotus punctulatus) accounted for a high proportion of interactions. Fruit set resulted mostly from pollination by winged insects, while flowers visited by ants did not set fruits. Thus, although ants were commonly seen on flowers, their effectiveness as pollinator was negligible for Condalia microphylla.